The nature of learning at forest school: practitioners' perspectives. Issue 2 (4th March 2017) - Harris, Frances
Abstract : This paper investigates forest school practitioners perceptions of learning at forest school to identify the topics covered, the learning styles, and the philosophies underpinning its delivery, based on interviews with experienced forest school practitioners. Practitioners identified the focus of learning at forest school as social development: teamwork, relationships with others, self-knowledge, and learning to take risks. Children also engaged with nature and developed an attachment to the woods where forest school took place. Learning styles were kinaesthetic, sensory, and experiential. Forest school leaders saw themselves as facilitators of learning rather than teachers.